Three methods of forecasting currency crises: Which made the run in signaling the South African currency crisis of June 2006? - Tobias Knedlik; Rolf Scheufele (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2007)
In this paper we test the ability of three of the most popular methods to forecast the South African currency crisis of June 2006. In particular we are interested in the out-ofsample performance of these methods. Thus, we choose the latest crisis to conduct an out-of-sample experiment. In sum, the signals approach was not able to forecast the outof- sample crisis of correctly; the probit approach was able to predict the crisis but just with models, that were based on raw data. Employing a Markov-regime-switching approach also allows to predict the out-of-sample crisis. The answer to the question of which method made the run in forecasting the June 2006 currency crisis is: the Markovswitching approach, since it called most of the pre-crisis periods correctly. However, the "victory" is not straightforward. In-sample, the probit models perform remarkably well and it is also able to detect, at least to some extent, out-of-sample currency crises before their occurrence. It can, therefore, not be recommended to focus on one approach only when evaluating the risk for currency crises. – – In diesem Beitrag wird die Prognosefähigkeit von drei populären Ansätzen anhand der südafrikanischen Währungskrise im Juni 2006 getestet. Von besonderem Interesse ist die Out-of-sample-Prognosegüte der Methoden. Deshalb wird die jüngste Währungskrise in Südafrika als Out-of-sample-Experiment genutzt. Im Ergebnis zeigt sich, dass der Signalansatz nicht in der Lage war die Währungskrise vorherzusagen; Probit-Ansätze konnten die Krise vorhersagen wenn sie auf Rohdaten und nicht auf Signalen des Signalansatzes basierten. Auch die Verwendung eines Markov-regime-switching-Ansatz führte zu korrenkten Prognosen der Out-of-sample-Krise. Die Antwort auf die Titelfrage des Beitrags, welche Methode die Krise vom Juni 2006 am besten vorhersagen konnte ist: der Markov-regime-switching-Ansatz, weil dieser die meisten Vorkrisenperioden korrekt erkannte. Dennoch ist der "Sieg" nicht überragend. So ist die In-sample-Prognosegüte des Probit-Ansatzes besser und dieser Ansatz ist auch in der Lage zumindest einige der Vorkrisenperioden als solche zu erkennen. Es kann daher nicht empfohlen werden Währungskrisenprognosen auf nur einen Ansatz zu stützen.
urn:nbn:de:gbv:3:2-6311
Keywords: C14; C22; C53; E47; F31; F37; 330; currency crisis; forecast; predictability; signals approach; Probit approach; Markov regime switching approach; South Africa; Währungskrise; Prognoseverfahren; Vergleich; Südafrika